STUDENTS WEBINAR PROJECT: AN AUTHENTIC ASSESMENT OF SPEAKING SKILL - Astrid Wangsagirindra Pudjastawa (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
This paper reports on one of the best practices in assessing students' speaking skills in the pandemic era. Given that speaking is a productive skill that should be assessed through authentic assessment, the teacher decided to assign students to create a students webinar project as part of their final exam. This project requires students to conduct real-life webinars where the organizer, speaker and audience are students themselves. To describe a related project the researcher combined qualitative and quantitative methods including peer feedback, interviews, self-reflection, and a learning satisfaction survey. Once implemented, it can be concluded that this project can be used as an alternative authentic assessment model that can be applied in the classroom that focuses on developing students' public speaking skills. This students webinar project is recommended not only because it can be used as an alternative assessment model but also encourages students to work together in teams and encourages them to work creatively, creating something new to work better. Another important thing obtained in the implementation is feedback from students, which is the main factor that can make them feel satisfied and motivate them to study effectively.